Socioeconomic and Psychosocial Adversities Experienced by Freelancers Working in the UK Cultural Sector During the COVID-19 Pandemic: A Qualitative Study - May, Tom; Warran, Katey; Burton, Alexandra; Fancourt, Daisy (Frontiers in Psychology, 2022)
There are concerns that the socioeconomic consequences of COVID-19, including unemployment and financial insecurity, are having adverse effects on the mental wellbeing of the population. One group particularly vulnerable to socioeconomic adversity during this period are those employed freelance within the creative and cultural industries. Many workers in the sector were already subject to income instability, erratic work schedules and a lack of economic security before the pandemic, and it is possible that COVID-19 may exacerbate pre-existing economic precarity. Through interviews with 20 freelancers working within the performing arts, visual arts, and film and television industries, this article explores the impact of the pandemic on their working lives. Findings suggest the pandemic is affecting the psychological wellbeing of freelancers through employment loss, financial instability and work dissonance, and illustrates the need for urgent economic and psychosocial support for those employed within this sector.